A steel strip with high wear-resistant coating and its processing technology
The process of irradiating the polytetrafluoroethylene powder and forming a double-layer coating through gamma rays has solved the problem of insufficient surface performance of the existing stainless steel belt, achieved the improvement of high wear and corrosion resistance, and simplified the process steps.
Patent Information
- Application Number
- CN202411806340.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The surface properties of existing stainless steel strips cannot meet the high requirements of industrial production for wear resistance, hardness and corrosion resistance, and the processing technology is complex and the effect is poor.
A processing technology is adopted to irradiate the polytetrafluoroethylene powder by gamma rays and form a double-layer plating layer on the surface of the stainless steel strip. First, the nickel layer plating solution A with nickel sulfate as the main salt is pre-plating, and then the nickel layer plating solution B with nickel sulfate and cobalt sulfate as the main salt is plating. The grafted polytetrafluoroethylene powder and graphene coated alumina and other components are improved to improve the wear and corrosion resistance of the plating.
High wear and corrosion resistance of stainless steel belt surfaces is achieved, process steps are simplified, and surface hardness and comprehensive performance are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel strips, in particular to a steel strip with a high wear-resistant coating and a processing technology thereof. Background Art
[0002] With the rapid development of modern manufacturing technology, the industrial field has put forward higher and higher requirements on the surface properties of various materials, especially the surface properties of stainless steel strips. Since stainless steel strips are widely used in industrial production, the actual application requirements for their wear resistance, hardness, corrosion resistance and other properties are relatively high. In order to improve the comprehensive surface performance of stainless steel strips, the existing technology generally modifies the surface of stainless steel strips through electroplating, laser cladding, functional coating spraying, hot dip plating and other processes to improve the surface wear resistance, hardness and corrosion resistance of stainless steel strips. However, the process steps are relatively complicated, and the prepared stainless steel strips cannot meet actual needs.
[0003] Therefore, based on this situation, the present application discloses a steel strip with a high wear-resistant coating and a processing technology thereof to solve the technical problem. Summary of the invention
[0004] The object of the present invention is to provide a steel strip with a high wear-resistant coating and a processing technology thereof, so as to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a processing technology of a steel strip with a high wear-resistant coating, comprising the following steps:
[0006] Step (1): taking polytetrafluoroethylene powder, irradiating it with Co60 gamma rays in an air atmosphere, mixing the irradiated polytetrafluoroethylene powder, deionized water and ethanol, and dispersing them for 20 to 30 minutes, adding acrylic acid, ammonium ferrous sulfate and concentrated sulfuric acid, ultrasonically oscillating for 3 to 5 minutes, reacting them in a water bath at 60 to 65° C. for 2 to 3 hours, washing and drying, and obtaining grafted polytetrafluoroethylene powder;
[0007] Step (2): taking a stainless steel strip, placing it in a degreasing agent for degreasing for 10 to 20 minutes, the degreasing temperature being 80 to 85° C., then placing the stainless steel strip in a hydrochloric acid solution for activation for 1 to 3 minutes, and then washing and drying with deionized water; placing the activated stainless steel strip in a nickel layer plating solution A for electroplating for 15 to 20 minutes, and then placing it in a nickel layer plating solution B for electroplating for 30 to 40 minutes, thereby obtaining a steel strip with a highly wear-resistant coating;
[0008] The nickel layer plating solution A and the nickel layer plating solution B both contain grafted polytetrafluoroethylene powder, and the amount of the grafted polytetrafluoroethylene powder is 20-30 g / L.
[0009] In a more optimized solution, in step (2), the amounts of the components of the nickel plating solution A are as follows: nickel sulfate 200-220 g / L, boric acid 25-30 g / L, sodium hypophosphite 25-30 g / L, aluminum oxide 55-65 g / L, grafted polytetrafluoroethylene powder 20-30 g / L, and surfactant 1-1.5 g / L.
[0010] In a more optimized solution, in step (2), the amounts of the components of the nickel layer plating solution B are as follows: nickel sulfate 200-220 g / L, cobalt sulfate 2-10 g / L, boric acid 25-30 g / L, sodium hypophosphite 25-30 g / L, graphene-coated alumina 15-25 g / L, alumina 55-65 g / L, grafted polytetrafluoroethylene powder 20-30 g / L, and surfactant 1-1.5 g / L.
[0011] In a more optimized solution, the surfactants are OP-10 and FC-203, and the mass ratio of OP-10 to FC-203 is 1:1.
[0012] In the optimized solution, in step (2), the electroplating temperature is 55-60°C and the cathode current density is 2-4A / dm 2 ; The components of the degreasing agent are: 30~35g / L sodium hydroxide, 20~25g / L sodium carbonate, 8~10g / L sodium phosphate, 8~10g / L sodium silicate, 1~2g / LOP-10.
[0013] In a more optimized solution, in step (1), the irradiation dose is 50-60 kGy; the volume ratio of ethanol to deionized water is 1:4; the mass ratio of polytetrafluoroethylene powder to acrylic acid is 1:(3-4); the amount of ammonium ferrous sulfate is 1-1.5 wt% of the total mass of the system; and the amount of concentrated sulfuric acid is 0.5-1 wt% of the total mass of the system.
[0014] The most optimized solution is that the preparation steps of graphene-coated alumina are as follows:
[0015] S1: Mix the nano-alumina with the ethanol solution, perform ultrasound for 20-30 min, add acetic acid, adjust the pH to 4-5, then add KH-550, reflux and stir at 75-80 °C for 8-10 h, collect the product by filtration, wash with deionized water and anhydrous ethanol, and dry in vacuo to obtain amino-alumina;
[0016] S2: Mix graphene oxide and deionized water, and ultrasonicate for 40-60 minutes to obtain a graphene aqueous solution; mix amino alumina and deionized water, and ultrasonically disperse for 20-30 minutes, then add the graphene aqueous solution, adjust the pH to 3-5 with hydrochloric acid, react at 50-60°C for 6-8 hours, let stand for 2-3 hours, collect the product by centrifugation, wash and dry, and then transfer to a tubular furnace, heat to 600-650°C in a nitrogen atmosphere, keep warm for 4-5 hours, and cool to obtain graphene-coated alumina.
[0017] In a more optimized solution, in S1, the ethanol solution is a mixed solution of ethanol and deionized water with a volume ratio of 9:1; the dosage of the nano-alumina and KH-550 is 0.5 g:8.5 mL; in S2, the mass ratio of the graphene oxide and amino-alumina is 1:(18~20); and the concentration of the graphene aqueous solution is 0.5~1 mg / mL.
[0018] A more optimized solution is a steel strip with a highly wear-resistant coating obtained by the processing technology described in any of the above items.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The invention discloses a processing technology for a steel strip with a high wear-resistant coating. The scheme uses a stainless steel strip as a substrate. The stainless steel strip can be selected as a cold-rolled steel strip or a hot-rolled steel strip, and the specific model can be limited according to actual application requirements. The invention first removes oil from the surface of the stainless steel strip, activates it with hydrochloric acid, and sequentially places it in a nickel layer plating solution A and a nickel layer plating solution B to form a double-layer coating by electroplating, wherein the nickel layer plating solution A contains nickel sulfate as a main salt, and a nickel layer is pre-plated on the surface of the stainless steel strip; the nickel layer plating solution B contains nickel sulfate and cobalt sulfate as main salts, and a nickel-cobalt coating is formed on the surface of the pre-nickel coating, so that a composite coating with excellent wear resistance is formed on the surface of the stainless steel strip, and the corrosion resistance of the stainless steel strip is also improved.
[0021] In this scheme, the dosage of each component of the nickel layer plating solution A is: nickel sulfate 200-220g / L, boric acid 25-30g / L, sodium hypophosphite 25-30g / L, aluminum oxide 55-65g / L, grafted polytetrafluoroethylene powder 20-30g / L, surfactant 1-1.5g / L; grafted polytetrafluoroethylene powder and surfactant are added, and the scheme first uses Co60 source gamma rays to irradiate polytetrafluoroethylene, and then grafts acrylic acid on the surface to obtain grafted polytetrafluoroethylene. At the same time, a surfactant is introduced into the system, and the surfactant is a compound of OP-10 and FC-203. Therefore, the grafted polytetrafluoroethylene powder in the system is very uniformly dispersed. At the same time, due to the presence of the grafted polytetrafluoroethylene powder, it can adsorb aluminum oxide and promote the deposition and embedding of aluminum oxide. Therefore, after the nickel layer plating solution A is electroplated, the pre-plated nickel layer formed is dense and uniform, and the hardness and corrosion resistance are very excellent.
[0022] On this basis, the scheme further introduces nickel plating solution B, and the dosage of each component of nickel plating solution B is: nickel sulfate 200~220g / L, cobalt sulfate 2~10g / L, boric acid 25~30g / L, sodium hypophosphite 25~30g / L, graphene-coated alumina 15~25g / L, alumina 55~65g / L, grafted polytetrafluoroethylene powder 20~30g / L, surfactant 1~1.5g / L. Nickel plating solution B not only contains grafted polytetrafluoroethylene powder, surfactant, alumina and other components, but also introduces graphene-coated alumina, using graphene-coated alumina to replace part of alumina, so as to further improve the surface wear resistance of the stainless steel strip, and the introduction of graphene also further improves the corrosion resistance of the stainless steel strip.
[0023] The invention discloses a processing technology for a steel strip with a high wear-resistant coating. The formula design of each component is suitable, and the process parameters and steps are simplified. The finally prepared stainless steel strip has high surface hardness, good wear resistance and excellent corrosion resistance. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In this embodiment, the stainless steel strip is a 430 stainless steel strip with a thickness of 0.25 mm; the average particle size of polytetrafluoroethylene powder is 0.2 μm; FC-203 is a cationic surfactant; the particle size of nano-alumina is 30-40 nm; graphene oxide (SE3522, Changzhou Sixth Element Materials Co., Ltd.)
[0026] Embodiment 1: A process for processing a steel strip having a highly wear-resistant coating, comprising the following steps:
[0027] Step (1): taking polytetrafluoroethylene powder, irradiating it with Co60 gamma rays in an air atmosphere, mixing the irradiated polytetrafluoroethylene powder, deionized water and ethanol, dispersing for 20 minutes, adding acrylic acid, inhibitor and concentrated sulfuric acid, ultrasonically oscillating for 5 minutes, reacting in a water bath at 60°C for 3 hours, washing and drying to obtain grafted polytetrafluoroethylene powder;
[0028] The irradiation dose is 50 kGy; the inhibitor is ammonium ferrous sulfate, the volume ratio of ethanol to deionized water is 1:4; the mass ratio of polytetrafluoroethylene powder to acrylic acid is 1:4, the amount of the inhibitor is 1.5wt% of the total mass of the system, and the amount of concentrated sulfuric acid is 0.8wt% of the total mass of the system.
[0029] Step (2): Take a stainless steel strip and place it in a degreasing agent for degreasing for 20 minutes at a degreasing temperature of 80°C. The components of the degreasing agent are: 30 g / L sodium hydroxide, 25 g / L sodium carbonate, 10 g / L sodium phosphate, 10 g / L sodium silicate, and 1.5 g / L O-10; then place the stainless steel strip in a hydrochloric acid solution (50 mL of concentrated hydrochloric acid is added to 50 mL of water) for activation for 3 minutes, and then wash and dry with deionized water; place the activated stainless steel strip in a nickel layer plating solution A for electroplating for 15 minutes, and then place it in a nickel layer plating solution B for electroplating for 40 minutes to obtain a steel strip with a high wear-resistant coating; the electroplating temperature is 55°C, and the cathode current density is 3A / dm 2 .
[0030] The dosage of each component of nickel plating solution A is: 200g / L nickel sulfate, 30g / L boric acid, 30g / L sodium hypophosphite, 60g / L aluminum oxide, 20g / L grafted polytetrafluoroethylene powder, and 1g / L surfactant. The dosage of each component of nickel plating solution B is: 210g / L nickel sulfate, 5g / L cobalt sulfate, 30g / L boric acid, 30g / L sodium hypophosphite, 15g / L graphene-coated aluminum oxide, 65g / L aluminum oxide, 25g / L grafted polytetrafluoroethylene powder, and 1g / L surfactant. The surfactants are OP-10 and FC-203, and the mass ratio of OP-10 to FC-203 is 1:1.
[0031] The preparation steps of graphene-coated alumina are as follows:
[0032] S1: 0.5 g of nano-alumina was mixed with 150 mL of ethanol solution, and ultrasonicated for 20 min. Acetic acid was added to adjust the pH to 4.5, and then 8.5 mL of KH-550 was added. The mixture was refluxed and stirred at 75°C for 10 h. The product was collected by filtration, washed with deionized water and anhydrous ethanol, and dried in vacuo to obtain amino alumina. The ethanol solution was a mixed solution of ethanol and deionized water in a volume ratio of 9:1.
[0033] S2: Mix graphene oxide and deionized water, and ultrasonicate for 40 minutes to obtain a graphene aqueous solution with a concentration of 0.5 mg / mL; mix amination aluminum oxide and deionized water, and ultrasonically disperse for 20 minutes, then add the graphene aqueous solution, adjust the pH to 4 with hydrochloric acid, react at 50°C for 8 hours, stand for 2 hours, collect the product by centrifugation, wash and dry, and then transfer to a tube furnace, heat to 650°C in a nitrogen atmosphere, keep warm for 4.5 hours, and cool to obtain graphene-coated aluminum oxide. The mass ratio of graphene oxide to amination aluminum oxide is 1:18.
[0034] Embodiment 2: A process for processing a steel strip having a highly wear-resistant coating, comprising the following steps:
[0035] Step (1): taking polytetrafluoroethylene powder, irradiating it with Co60 gamma rays in an air atmosphere, mixing the irradiated polytetrafluoroethylene powder, deionized water and ethanol, dispersing for 25 minutes, adding acrylic acid, inhibitor and concentrated sulfuric acid, ultrasonically oscillating for 5 minutes, reacting in a water bath at 65°C for 2.5 hours, washing and drying to obtain grafted polytetrafluoroethylene powder;
[0036] The irradiation dose is 50 kGy; the inhibitor is ammonium ferrous sulfate, the volume ratio of ethanol to deionized water is 1:4; the mass ratio of polytetrafluoroethylene powder to acrylic acid is 1:4, the amount of the inhibitor is 1.5wt% of the total mass of the system, and the amount of concentrated sulfuric acid is 0.8wt% of the total mass of the system.
[0037] Step (2): Take a stainless steel strip and place it in a degreasing agent for degreasing for 15 minutes. The degreasing temperature is 85°C. The components of the degreasing agent are: 30 g / L sodium hydroxide, 25 g / L sodium carbonate, 10 g / L sodium phosphate, 10 g / L sodium silicate, and 1.5 g / L O-10; then place the stainless steel strip in a hydrochloric acid solution (50 mL of concentrated hydrochloric acid is added to 50 mL of water) for activation for 3 minutes, and then wash and dry with deionized water; place the activated stainless steel strip in a nickel layer plating solution A for electroplating for 18 minutes, and then place it in a nickel layer plating solution B for electroplating for 40 minutes to obtain a steel strip with a high wear-resistant coating; the electroplating temperature is 55°C, and the cathode current density is 3A / dm 2 .
[0038] The dosage of each component of nickel plating solution A is: nickel sulfate 200g / L, boric acid 30g / L, sodium hypophosphite 30g / L, aluminum oxide 60g / L, grafted polytetrafluoroethylene powder 20g / L, surfactant 1g / L. The dosage of each component of nickel plating solution B is: nickel sulfate 210g / L, cobalt sulfate 5g / L, boric acid 30g / L, sodium hypophosphite 30g / L, graphene coated aluminum oxide 20g / L, aluminum oxide 60g / L, grafted polytetrafluoroethylene powder 25g / L, surfactant 1g / L. The surfactants are OP-10 and FC-203, and the mass ratio of OP-10 to FC-203 is 1:1.
[0039] The preparation steps of graphene-coated alumina are as follows:
[0040] S1: 0.5 g of nano-alumina was mixed with 150 mL of ethanol solution, and ultrasonicated for 25 min. Acetic acid was added to adjust the pH to 4.5, and then 8.5 mL of KH-550 was added. The mixture was refluxed and stirred at 75 °C for 9 h. The product was collected by filtration, washed with deionized water and anhydrous ethanol, and dried in vacuo to obtain amino alumina. The ethanol solution was a mixed solution of ethanol and deionized water in a volume ratio of 9:1.
[0041] S2: Mix graphene oxide and deionized water, and ultrasonicate for 50 minutes to obtain a graphene aqueous solution with a concentration of 0.5 mg / mL; mix amination aluminum oxide and deionized water, and ultrasonically disperse for 25 minutes, then add the graphene aqueous solution, adjust the pH to 4 with hydrochloric acid, react at 55°C for 7 hours, let stand for 2 hours, collect the product by centrifugation, wash and dry, and then transfer to a tube furnace, heat to 650°C in a nitrogen atmosphere, keep warm for 4.5 hours, and cool to obtain graphene-coated aluminum oxide. The mass ratio of graphene oxide to amination aluminum oxide is 1:18.
[0042] Embodiment 3: A process for processing a steel strip having a highly wear-resistant coating, comprising the following steps:
[0043] Step (1): taking polytetrafluoroethylene powder, irradiating it with Co60 gamma rays in an air atmosphere, mixing the irradiated polytetrafluoroethylene powder, deionized water and ethanol, and dispersing them for 30 minutes, adding acrylic acid, an inhibitor and concentrated sulfuric acid, ultrasonically oscillating for 5 minutes, reacting them in a water bath at 65°C for 2 hours, washing and drying, and obtaining grafted polytetrafluoroethylene powder;
[0044] The irradiation dose is 50 kGy; the inhibitor is ammonium ferrous sulfate, the volume ratio of ethanol to deionized water is 1:4; the mass ratio of polytetrafluoroethylene powder to acrylic acid is 1:4, the amount of the inhibitor is 1.5wt% of the total mass of the system, and the amount of concentrated sulfuric acid is 0.8wt% of the total mass of the system.
[0045] Step (2): Take a stainless steel strip and place it in a degreasing agent for degreasing for 20 minutes at a degreasing temperature of 80°C. The components of the degreasing agent are: 30 g / L sodium hydroxide, 25 g / L sodium carbonate, 10 g / L sodium phosphate, 10 g / L sodium silicate, and 1.5 g / L O-10; then place the stainless steel strip in a hydrochloric acid solution (50 mL of concentrated hydrochloric acid is added to 50 mL of water) for activation for 3 minutes, and then wash and dry with deionized water; place the activated stainless steel strip in a nickel layer plating solution A for electroplating for 20 minutes, and then place it in a nickel layer plating solution B for electroplating for 40 minutes to obtain a steel strip with a high wear-resistant coating; the electroplating temperature is 55°C, and the cathode current density is 3A / dm 2 .
[0046] The dosage of each component of nickel plating solution A is: 200g / L nickel sulfate, 30g / L boric acid, 30g / L sodium hypophosphite, 60g / L aluminum oxide, 20g / L grafted polytetrafluoroethylene powder, and 1g / L surfactant. The dosage of each component of nickel plating solution B is: 210g / L nickel sulfate, 5g / L cobalt sulfate, 30g / L boric acid, 30g / L sodium hypophosphite, 25g / L graphene-coated aluminum oxide, 55g / L aluminum oxide, 30g / L grafted polytetrafluoroethylene powder, and 1g / L surfactant. The surfactants are OP-10 and FC-203, and the mass ratio of OP-10 to FC-203 is 1:1.
[0047] The preparation steps of graphene-coated alumina are as follows:
[0048] S1: 0.5 g of nano-alumina was mixed with 150 mL of ethanol solution, and ultrasonicated for 30 min. Acetic acid was added to adjust the pH to 4.5, and then 8.5 mL of KH-550 was added. The mixture was refluxed and stirred at 80°C for 8 h. The product was collected by filtration, washed with deionized water and anhydrous ethanol, and dried in vacuo to obtain amino alumina. The ethanol solution was a mixed solution of ethanol and deionized water in a volume ratio of 9:1.
[0049] S2: Mix graphene oxide and deionized water, and ultrasonicate for 60 minutes to obtain a graphene aqueous solution with a concentration of 0.5 mg / mL; mix amination aluminum oxide and deionized water, and ultrasonically disperse for 20 minutes, then add the graphene aqueous solution, adjust the pH to 4 with hydrochloric acid, react at 60°C for 6 hours, stand for 2 hours, collect the product by centrifugation, wash and dry, and then transfer to a tube furnace, heat to 650°C in a nitrogen atmosphere, keep warm for 4.5 hours, and cool to obtain graphene-coated aluminum oxide. The mass ratio of graphene oxide to amination aluminum oxide is 1:18.
[0050] Comparative Example 1: A processing technology for a steel strip with a high wear-resistant coating, comprising the following steps:
[0051] Step (1): taking polytetrafluoroethylene powder, irradiating it with Co60 gamma rays in an air atmosphere, mixing the irradiated polytetrafluoroethylene powder, deionized water and ethanol, and dispersing them for 30 minutes, adding acrylic acid, an inhibitor and concentrated sulfuric acid, ultrasonically oscillating for 5 minutes, reacting them in a water bath at 65°C for 2 hours, washing and drying, and obtaining grafted polytetrafluoroethylene powder;
[0052] The irradiation dose is 50 kGy; the inhibitor is ammonium ferrous sulfate, the volume ratio of ethanol to deionized water is 1:4; the mass ratio of polytetrafluoroethylene powder to acrylic acid is 1:4, the amount of the inhibitor is 1.5wt% of the total mass of the system, and the amount of concentrated sulfuric acid is 0.8wt% of the total mass of the system.
[0053] Step (2): Take a stainless steel strip and place it in a degreasing agent for degreasing for 20 minutes at a degreasing temperature of 80°C. The components of the degreasing agent are: 30 g / L sodium hydroxide, 25 g / L sodium carbonate, 10 g / L sodium phosphate, 10 g / L sodium silicate, and 1.5 g / L O-10; then place the stainless steel strip in a hydrochloric acid solution (50 mL of concentrated hydrochloric acid is added to 50 mL of water) for activation for 3 minutes, and then wash and dry with deionized water; place the activated stainless steel strip in a nickel layer plating solution A for electroplating for 20 minutes, and then place it in a nickel layer plating solution B for electroplating for 40 minutes to obtain a steel strip with a high wear-resistant coating; the electroplating temperature is 55°C, and the cathode current density is 3A / dm 2 .
[0054] The dosage of each component of nickel plating solution A is: 200g / L nickel sulfate, 30g / L boric acid, 30g / L sodium hypophosphite, 60g / L aluminum oxide, 20g / L grafted polytetrafluoroethylene powder, and 1g / L surfactant. The dosage of each component of nickel plating solution B is: 210g / L nickel sulfate, 5g / L cobalt sulfate, 30g / L boric acid, 30g / L sodium hypophosphite, 65g / L aluminum oxide, 30g / L grafted polytetrafluoroethylene powder, and 1g / L surfactant. The surfactants are OP-10 and FC-203, and the mass ratio of OP-10 to FC-203 is 1:1.
[0055] Comparative Example 1 is a control example of Example 3, and graphene-coated alumina is not added to Comparative Example 1.
[0056] Comparative Example 2: A process for processing a steel strip having a highly wear-resistant coating, comprising the following steps:
[0057] Step (1): taking polytetrafluoroethylene powder, irradiating it with Co60 gamma rays in an air atmosphere, mixing the irradiated polytetrafluoroethylene powder, deionized water and ethanol, and dispersing them for 30 minutes, adding acrylic acid, an inhibitor and concentrated sulfuric acid, ultrasonically oscillating for 5 minutes, reacting them in a water bath at 65°C for 2 hours, washing and drying, and obtaining grafted polytetrafluoroethylene powder;
[0058] The irradiation dose is 50 kGy; the inhibitor is ammonium ferrous sulfate, the volume ratio of ethanol to deionized water is 1:4; the mass ratio of polytetrafluoroethylene powder to acrylic acid is 1:4, the amount of the inhibitor is 1.5wt% of the total mass of the system, and the amount of concentrated sulfuric acid is 0.8wt% of the total mass of the system.
[0059] Step (2): Take a stainless steel strip and place it in a degreasing agent for degreasing for 20 minutes at a degreasing temperature of 80°C. The components of the degreasing agent are: 30 g / L sodium hydroxide, 25 g / L sodium carbonate, 10 g / L sodium phosphate, 10 g / L sodium silicate, and 1.5 g / L O-10; then place the stainless steel strip in a hydrochloric acid solution (50 mL of concentrated hydrochloric acid is added to 50 mL of water) for activation for 3 minutes, and then wash and dry with deionized water; place the activated stainless steel strip in a nickel layer plating solution A for electroplating for 20 minutes, and then place it in a nickel layer plating solution B for electroplating for 40 minutes to obtain a steel strip with a high wear-resistant coating; the electroplating temperature is 55°C, and the cathode current density is 3A / dm 2 .
[0060] The dosage of each component of nickel plating solution A is: nickel sulfate 200g / L, boric acid 30g / L, sodium hypophosphite 30g / L, aluminum oxide 60g / L, grafted polytetrafluoroethylene powder 20g / L, surfactant 1g / L. The dosage of each component of nickel plating solution B is: nickel sulfate 210g / L, cobalt sulfate 5g / L, boric acid 30g / L, sodium hypophosphite 30g / L, graphene coated aluminum oxide 25g / L, aluminum oxide 55g / L, grafted polytetrafluoroethylene powder 30g / L, surfactant 1g / L. The surfactant is OP-10.
[0061] The preparation steps of graphene-coated alumina are as follows:
[0062] S1: 0.5 g of nano-alumina was mixed with 150 mL of ethanol solution, and ultrasonicated for 30 min. Acetic acid was added to adjust the pH to 4.5, and then 8.5 mL of KH-550 was added. The mixture was refluxed and stirred at 80°C for 8 h. The product was collected by filtration, washed with deionized water and anhydrous ethanol, and dried in vacuo to obtain amino alumina. The ethanol solution was a mixed solution of ethanol and deionized water in a volume ratio of 9:1.
[0063] S2: Mix graphene oxide and deionized water, and ultrasonicate for 60 minutes to obtain a graphene aqueous solution with a concentration of 0.5 mg / mL; mix amination aluminum oxide and deionized water, and ultrasonically disperse for 20 minutes, then add the graphene aqueous solution, adjust the pH to 4 with hydrochloric acid, react at 60°C for 6 hours, stand for 2 hours, collect the product by centrifugation, wash and dry, and then transfer to a tube furnace, heat to 650°C in a nitrogen atmosphere, keep warm for 4.5 hours, and cool to obtain graphene-coated aluminum oxide. The mass ratio of graphene oxide to amination aluminum oxide is 1:18.
[0064] Comparative Example 2 is a control example of Example 3. In Comparative Example 2, no FC-203 surfactant was added, and only OP-10 surfactant was added.
[0065] Comparative Example 3: A process for processing a steel strip having a highly wear-resistant coating, comprising the following steps:
[0066] Step (1): Take a stainless steel strip and place it in a degreasing agent for degreasing for 20 minutes, the degreasing temperature is 80°C, and the components of the degreasing agent are: 30g / L sodium hydroxide, 25g / L sodium carbonate, 10g / L sodium phosphate, 10g / L sodium silicate, and 1.5g / L O-10; then place the stainless steel strip in a hydrochloric acid solution (50mL concentrated hydrochloric acid is added to 50mL water) for activation for 3 minutes, and then wash and dry with deionized water; place the activated stainless steel strip in a nickel layer plating solution A for electroplating for 20 minutes, and then place it in a nickel layer plating solution B for electroplating for 40 minutes to obtain a steel strip with a high wear-resistant coating; the electroplating temperature is 55°C, and the cathode current density is 3A / dm 2 .
[0067] The dosage of each component of nickel plating solution A is: 200g / L nickel sulfate, 30g / L boric acid, 30g / L sodium hypophosphite, 60g / L aluminum oxide, 20g / L polytetrafluoroethylene powder, and 1g / L surfactant. The dosage of each component of nickel plating solution B is: 210g / L nickel sulfate, 5g / L cobalt sulfate, 30g / L boric acid, 30g / L sodium hypophosphite, 25g / L graphene-coated aluminum oxide, 55g / L aluminum oxide, 30g / L polytetrafluoroethylene powder, and 1g / L surfactant. The surfactants are OP-10 and FC-203, and the mass ratio of OP-10 to FC-203 is 1:1.
[0068] The preparation steps of graphene-coated alumina are as follows:
[0069] S1: 0.5 g of nano-alumina was mixed with 150 mL of ethanol solution, and ultrasonicated for 30 min. Acetic acid was added to adjust the pH to 4.5, and then 8.5 mL of KH-550 was added. The mixture was refluxed and stirred at 80°C for 8 h. The product was collected by filtration, washed with deionized water and anhydrous ethanol, and dried in vacuo to obtain amino alumina. The ethanol solution was a mixed solution of ethanol and deionized water in a volume ratio of 9:1.
[0070] S2: Mix graphene oxide and deionized water, and ultrasonicate for 60 minutes to obtain a graphene aqueous solution with a concentration of 0.5 mg / mL; mix amination aluminum oxide and deionized water, and ultrasonically disperse for 20 minutes, then add the graphene aqueous solution, adjust the pH to 4 with hydrochloric acid, react at 60°C for 6 hours, stand for 2 hours, collect the product by centrifugation, wash and dry, and then transfer to a tube furnace, heat to 650°C in a nitrogen atmosphere, keep warm for 4.5 hours, and cool to obtain graphene-coated aluminum oxide. The mass ratio of graphene oxide to amination aluminum oxide is 1:18.
[0071] Comparative Example 3 is a control example of Example 3. In Comparative Example 3, polytetrafluoroethylene powder is not grafted, and only polytetrafluoroethylene powder is added.
[0072] Detection experiment:
[0073] 1. Prepare steel strip samples according to Examples 1 to 3 and Comparative Examples 1 to 3, and detect the hardness of the coating on the surface of the samples. The load is 50 g, the holding time is 10 s, and the average value is taken after testing 3 to 5 different positions.
[0074] 2. Prepare steel strip samples according to Examples 1 to 3 and Comparative Examples 1 to 3, and detect the friction coefficient of the sample surface. The grinding balls are zirconium dioxide grinding balls with a diameter of 3 mm. The test load is 100 g, the rotation speed is 200 r / min, the test radius is 3 mm, and the test time is 15 min.
[0075] 3. Prepare steel strip samples according to Examples 1 to 3 and Comparative Examples 1 to 3, immerse the samples in a 3.5 wt% NaCl solution, take them out after immersion for 7 days, wipe off the surface moisture and weigh them, and calculate the mass loss before and after the test.
[0076]
[0077] Conclusion: The scheme uses stainless steel strip as the substrate, and the stainless steel strip can be selected as cold-rolled steel strip or hot-rolled steel strip, and the specific model can be limited according to the actual application requirements; the invention first degreases the surface of the stainless steel strip, activates it with hydrochloric acid, and places it in nickel plating solution A and nickel plating solution B in turn, and electroplating forms a double-layer coating, wherein nickel plating solution A contains nickel sulfate as the main salt, and a nickel layer is pre-plated on the surface of the stainless steel strip; nickel plating solution B contains nickel sulfate and cobalt sulfate as the main salts, and a nickel-cobalt coating is formed on the surface of the pre-nickel coating, thereby forming a composite coating with excellent wear resistance on the surface of the stainless steel strip, and the corrosion resistance of the stainless steel strip is also improved.
[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A process for processing a steel strip having a highly wear-resistant coating, characterized in that: The following steps are involved: Step (1): taking polytetrafluoroethylene powder, irradiating it with Co60 gamma rays in an air atmosphere, mixing the irradiated polytetrafluoroethylene powder, deionized water and ethanol, and dispersing them for 20 to 30 minutes, adding acrylic acid, ammonium ferrous sulfate and concentrated sulfuric acid, ultrasonically oscillating for 3 to 5 minutes, reacting them in a water bath at 60 to 65° C. for 2 to 3 hours, washing and drying, and obtaining grafted polytetrafluoroethylene powder; Step (2): taking a stainless steel strip, placing it in a degreasing agent for degreasing for 10 to 20 minutes, the degreasing temperature being 80 to 85° C., then placing the stainless steel strip in a hydrochloric acid solution for activation for 1 to 3 minutes, and then washing and drying with deionized water; placing the activated stainless steel strip in a nickel layer plating solution A for electroplating for 15 to 20 minutes, and then placing it in a nickel layer plating solution B for electroplating for 30 to 40 minutes, thereby obtaining a steel strip with a highly wear-resistant coating; The nickel layer plating solution A and the nickel layer plating solution B both contain grafted polytetrafluoroethylene powder, and the amount of grafted polytetrafluoroethylene powder is 20-30 g / L; In step (2), the amounts of the components of nickel plating solution A are: nickel sulfate 200-220 g / L, boric acid 25-30 g / L, sodium hypophosphite 25-30 g / L, aluminum oxide 55-65 g / L, grafted polytetrafluoroethylene powder 20-30 g / L, and surfactant 1-1.5 g / L; the amounts of the components of nickel plating solution B are: nickel sulfate 200-220 g / L, cobalt sulfate 2-10 g / L, boric acid 25-30 g / L, sodium hypophosphite 25-30 g / L, graphene-coated aluminum oxide 15-25 g / L, aluminum oxide 55-65 g / L, grafted polytetrafluoroethylene powder 20-30 g / L, and surfactant 1-1.5 g / L; The surfactants are OP-10 and FC-203, and the mass ratio of OP-10 to FC-203 is 1:
1.
2. A process for processing a steel strip with a high wear-resistant coating according to claim 1, characterized in that: In step (2), the electroplating temperature is 55-60°C and the cathode current density is 2-4A / dm 2 ; The components of the degreasing agent are: 30~35g / L sodium hydroxide, 20~25g / L sodium carbonate, 8~10g / L sodium phosphate, 8~10g / L sodium silicate, 1~2g / LOP-10.
3. The process for processing a steel strip having a high wear-resistant coating according to claim 1, characterized in that: In step (1), the irradiation dose is 50-60 kGy; the mass ratio of the polytetrafluoroethylene powder to the acrylic acid is 1:(3-4), the amount of the ammonium ferrous sulfate used is 1-1.5 wt% of the total mass of the system, and the amount of the concentrated sulfuric acid used is 0.5-1 wt% of the total mass of the system.
4. The process for processing a steel strip with a high wear-resistant coating according to claim 1, characterized in that: The preparation steps of graphene-coated alumina are: S1: Mix the nano-alumina with the ethanol solution, perform ultrasound for 20-30 min, add acetic acid, adjust the pH to 4-5, then add KH-550, reflux and stir at 75-80 °C for 8-10 h, collect the product by filtration, wash with deionized water and anhydrous ethanol, and dry in vacuo to obtain amino-alumina; S2: Mix graphene oxide and deionized water, and ultrasonicate for 40-60 minutes to obtain a graphene oxide aqueous solution; mix amino alumina and deionized water, and ultrasonically disperse for 20-30 minutes, then add the graphene oxide aqueous solution, adjust the pH to 3-5 with hydrochloric acid, react at 50-60°C for 6-8 hours, let stand for 2-3 hours, collect the product by centrifugation, wash and dry, and then transfer to a tubular furnace, heat to 600-650°C in a nitrogen atmosphere, keep warm for 4-5 hours, and cool to obtain graphene-coated alumina.
5. The process for processing a steel strip with a high wear-resistant coating according to claim 4, characterized in that: In S1, the ethanol solution is a mixed solution of ethanol and deionized water; in S2, the mass ratio of graphene oxide to amino-alumina is 1:(18-20); and the concentration of the graphene oxide aqueous solution is 0.5-1 mg / mL.
6. A steel strip having a highly wear-resistant coating obtained by the processing technology according to any one of claims 1 to 5.
Citation Information
Patent Citations
Method for performing chemical plating on surface of polytetrafluoroethylene thin film
CN101974741A
Hydrophilic heat-resistant polytetrafluoroethylene micro-powder and preparation method thereof
CN106957391A